PSAK 73 on Leases in Financial Statements: A Case Study of a Multinational Healthcare Company - Dassaad; Budi Wahyudi; Dyah Palupi; Riyanti (Global Writing Academica Researching & Publishing, 2023)
Starting January 1, 2020, the updated lease accounting standards must be applied by all entities under PSAK 73. PSAK 73 was made because the previous lease treatment considered to be less transparent and could not meet the needs of users of financial statements related to leases made by lessees so that many users made their own adjustments to the financial statements for the lessee's side by capitalizing operating leases using limited information contained in the notes to the financial statements. The capitalization of right-of-use assets and lease liabilities results in changes to the balance sheet position and incurs rental costs, thereby affecting the income statement. The author analyzes the impact of lease accounting standards using a comparative descriptive method. This study uses primary and quantitative data in the form of financial statements of PT. GAHC from year 2019 to year 2022. The purpose of this study is to determine the application of PSAK 73 to leasing and the impact on the financial statements of PT. GAHC and look at the leverage ratio and profitability ratio of PT. GAHC. The results of the study show that the implementation of PSAK 73 at PT. GAHC from 2020 to 2022 has no significant effect on the financial statements and financial ratios due to the value of the lease liability of PT. GAHC is immaterial.